PENGEMBANGAN BAHAN AJAR MENULIS BIPA TINGKAT MADYA TINGGI BERBASIS KONTEKS LINGKUNGAN PELAJAR - Rina Rizki Amalia; Imam Suyitno; Kusubakti Andajani (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This development research aims to produce an intermediate high level BIPA writing teaching material product based on the context of the learner's environment that has gone through a validation test. This research adapts Thiagarajan's 4D development model and is limited to the revision stage based on the assessment of expert validators and practitioners. Based on the validation results, an average percentage of 81.25% was obtained in the content feasibility aspect, an average percentage of 83.3% was obtained in the presentation feasibility aspect, an average percentage of 75% was obtained in the language feasibility aspect, and an average percentage of 81.06% was obtained in the display feasibility aspect. From the overall total validation results with an average percentage of 80.15%, it can be concluded that the teaching materials for writing intermediate high level BIPA based on the context of the learner's environment can be said to be feasible to use.